2021
DOI: 10.1186/s12889-021-12296-1
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of paediatric burn injuries: a systematic review

Abstract: Objective To review and synthesise qualitative literature regarding the psychological outcomes following paediatric burn injuries, and to determine if children and adolescents who experience a burn injury have elevated risk of psychopathology following the injury. Design Systematic review of quantitative and qualitative studies. Data sources Informit health, Medline, Embase, and PsycINFO were searched … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 73 publications
2
38
0
Order By: Relevance
“…Burn injuries can have significant psychological, social, and economic impacts on a child's life and the lives of their caregivers ( 16 ). Data regarding pediatric global burn trends is inconsistent and frequently extrapolated from single-center or country-specific studies that fail to provide a clear understanding of the global problem ( 15 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Burn injuries can have significant psychological, social, and economic impacts on a child's life and the lives of their caregivers ( 16 ). Data regarding pediatric global burn trends is inconsistent and frequently extrapolated from single-center or country-specific studies that fail to provide a clear understanding of the global problem ( 15 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequences of burn injuries can extend beyond the acute healing phase3 with lasting effects on health, including hypermetabolism and an increased risk of chronic disease leading to a reduced life span 4. Additionally, burn injuries may result in worsened social and psychological outcomes such as anxiety, post-traumatic stress, depression and reduced quality of life 5…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that burn injuries are traumatic experiences that can detrimentally impact an individual's psychological and emotional wellbeing. Posttraumatic stress disorder occurs in 8 to 30% of the adult burn population [2], and 11 to 13% of child burn populations [3], and routine clinical practice accepts the absence of a mental health disorder as an acceptable goal. However, research has shown that postburn hospital admission rates for mental health conditions were 3.52-6.79 times as high compared to a matched uninjured cohort, suggesting that the absence of a diagnosed mental health is not adequate for optimal mental health recovery [4].…”
Section: Introductionmentioning
confidence: 99%